ULTRAHIGH TEMPERATURE DEFORMATION MICROSTRUCTURES IN FELSIC GRANULITES OF THE NAPIER COMPLEX, ANTARCTICA - Lund M.D.; Piazolo S.; Harley S.L. (My University, 2006)
Detailed electron microscope and microstructural analysis of two ultrahigh temperature felsic granulites from Tonagh Island, Napier Complex, Antarctica show deformation microstructures produced at ~ 1000 °C at 8-10 kbar. High temperature orthopyroxene (Al ~7 wt.% and ~ 11 wt.%), exhibits crystallographic preferred orientation (CPO) and frequent subgrain boundaries which point to dislocation creep as the dominating deformation mechanism within opx. Two different main slip systems are observed: in opx bands with exclusively opx grains containing subgrain boundaries with traces parallel to [010] and a strong coupling of low angle misorientations (2.5°-5°) with rotation axes parallel to [010] the dominating slip system is (100)[001]. Isolated opx grains and grain clusters of 2-5 grains embedded in a qtz-fsp matrix show an additional slip system of (010)[001]. The latter slip system is harder to activate. We suggest that differences in the activation of these slip systems is a result of higher differential stresses imposed onto the isolated opx grains and grain clusters. In contrast to opx, large qtz grains (up to 200 μm) show random crystallographic orientation. This together with their elongate and cuspate shape and the lack of systematic in the rotation axes associated with the subgrain boundaries is consistent with diffusion creep as the primary deformation mechanism in quartz. Our first time detailed microstructural observations of ultrahigh temperature and medium to high pressure granulites and their interpretation in terms of active deformation mechanisms give some insight into the type of rheology that can be expect at lower crustal conditions. If qtz is the mineral phase governing the rock rheology, Newtonian flow behaviour is expected and only low differential stress can be supported. However, if the stress supporting mineral phase is opx, the flow law resulting from dislocation creep will govern the rheology of the rock unit; hence, an exponential relationship between stress and strain rate is to be expected. © 2006 Elsevier B.V. All rights reserved.
Keywords: AL DIFFUSION; DEFORMATION MECHANISM; FELSIC GRANULITES; MICROSTRUCTURE; ORTHOPYROXENE SLIP SYSTEMS; ULTRAHIGH TEMPERATURE